Pengembangan E-LKPD Berbasis SOLE (Self Organized Learning Environment) Menggunakan Live Work Sheets pada Materi Asam Basa Kelas XI SMA/MA Sederajat - Septia, Fatimah; Sri Haryati; Lenny Anwar (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to develop an E-LKPD (Electronic Student Worksheet) employing a Self Organized Learning Environment (SOLE) approach, specifically tailored with Liveworksheets for the acid-base topic aimed at XI grade high school or MA equivalent students. The research is centered on research and development, employing a 4-D development model that includes four phases: Definition, Design, Development, and Dissemination. This research involved one-on-one trials, teacher response tests, and small group trials to improve the development process. The study was carried out at FKIP University of Riau, along with SMAN 15 Pekanbaru and SMAN 7 Pekanbaru. This research examines the SOLE-based E-LKPD format. The data collection instruments included validation sheets given to three validators: two material experts and one media expert. User response sheets were distributed to two chemistry teachers and twenty students. The study produced an average score of 86.42% from material experts and a perfect score of 100% from media experts, both classified as valid. The trial results indicated an average percentage score of 95.1% for teachers and 90.71% for students, both categorized as very good. The study's findings demonstrate that SOLE-based E-LKPD using Liveworksheets for acid-base materials functions effectively as a learning medium.